2000
DOI: 10.1063/1.372425
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plasma etching on the noise performance of Ti/p-Si and Ti/p-Si1−xGex Schottky contacts

Abstract: The effect of plasma etching on the noise properties of Ti/p-Si and Ti/p-Si1−xGex (with x=0.05) Schottky junctions has been investigated. The noise measurements were performed over a temperature range of 77–300 K at frequencies of 10–100 kHz. The main noise source observed in these diodes during argon plasma sputter etching was attributed to the generation–recombination noise. From the analysis of the noise data, we have determined the interface state density and evaluated the introduced damage. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…For example, the studies of Ouacha et al 22,23 on Ir/p-Si and Singh and Kanjilal 24 on Pd/ n-GaAs showed a clear dependence of 1/f noise on temperature. Temperature dependent noise behaviour in both the diodes (Ir/p-Si and Pd/n-GaAs) was not in agreement with the Hsu's model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the studies of Ouacha et al 22,23 on Ir/p-Si and Singh and Kanjilal 24 on Pd/ n-GaAs showed a clear dependence of 1/f noise on temperature. Temperature dependent noise behaviour in both the diodes (Ir/p-Si and Pd/n-GaAs) was not in agreement with the Hsu's model.…”
Section: Introductionmentioning
confidence: 99%
“…10 The noise power density S I at a frequency f then can be expressed for a given bias V and dc current I as 10…”
Section: Resultsmentioning
confidence: 99%
“…Lao's model attributed the 1/f noise to the mobility and diffusivity fluctuations of the carriers within the space charge region. 10 According to this model the noise power density should increase with the increase in temperature. However, in many cases we observe the reverse behavior, that is, decrease in noise with increase in temperature.…”
mentioning
confidence: 99%
“…31,33 The factor ␥ H / N has been used to characterize plasma etching-induced sidewall damage. 31,33 The factor ␥ H / N has been used to characterize plasma etching-induced sidewall damage.…”
Section: Introductionmentioning
confidence: 99%